Happiness and employee performance: the moderating role of employee spirituality and emotional wellness - Ibrahim Awada, Nesreen (2021)
While happiness is a primary goal in life, few studies have examined its effect on employee performance (EP). This study looks at the effect of employee happiness (EH) on the EP of public sector employees in the United Arab Emirates (UAE), while examining the moderating role of their spiritual and emotional wellness (ESEW). Theory Y, Two-Factor Theory, and Job Characteristic Model were reviewed, as well as frameworks related to EP. Based on these theories and current literature, the study proposed that happiness positively affects the ESEW, impacting their performance. EH was operationalized to include seven sub-constructs: performance appraisal, promotion, rewards and recognition, income, workload, flexible working hours, workplace environment, and peer and supervisor support. Each was presumed to affect EP. In addition, ESEW is expected to moderate the effect of EH on EP. The population of this study was public servants in Abu Dhabi and Dubai, for which a random sampling technique was deployed. The instrument of data collection was a questionnaire. The questionnaire was validated, and a pilot study conducted, prior to data collection. Data was collected from 334 respondents and examined using the Statistical Package for Social Science (SPSS) version 22.0. Hypotheses were tested using Smart Partial Least Square (Smart PLS). Findings confirmed that EH has a significant effect on EP, as well as ESEW. ESEW did not have a significant effect on EP, but it moderated the effect of EH on EP. The study recommends that decision makers increase EH by appraising performance fairly and providing a competitive salary. It concludes with a discussion of the findings, limitations and directions for future work.